Kemampuan Menulis Makalah Ilmiah pada Mata Kuliah Psikolinguistik Mahasiswa Prodi Pendidikan Bahasa dan Sastra Indonesia (PBSI) FKIP Universitas PGRI Yogyakarta - Ari Wulandari; Susetyo; Rika Novita Kusumaningrum (Sasdaya: Gadjah Mada Journal of Humanities, 2022)
The objectives of this study are to determine the ability of students Pendidikan Bahasa dan Sastra Indonesia (PBSI), FKIP, Universitas PGRI Yogyakarta (UPY) in writing scientific papers; and to find out the difficulties of students in writing scientific papers. The research method used is descriptive qualitative. The population in this study were PBSI students who were conducted in the odd semester of the 2021/2022 academic year. The sample is 31 students of class G-1 who take Psycholinguistics courses. Data in the form of scientific papers were collected in the middle of the semester of Psycholinguistics lectures. The scientific paper was analyzed using research instruments. The writing ability assessed includes five aspects, namely (1) ideas, (2) organization, (3) grammar, (4) diction, and (5) spelling. Based on the assessment, each is categorized into five, namely (1) very good with a score range of 86-100, (2) good with a score range of 68-85, (3) sufficient with a score range of 48-67, (4) less with range of values from 32 to 47, and (5) very less with a range of values <32. The results of this study stated that 31 students or 100% got an average score of 78.15 with the highest score of 83 and the lowest score of 72. This category of scores was included in good. Their abilities in expressing ideas, organization of essays, and choosing diction are good. Their shortcomings are average in terms of grammar and spelling.